Heterotopie i nie-miejsca w „Cześć Tereska!” Roberta Glińskiego i „Lilji 4-ever” Lukasa Moodyssona - Svensson, My (Studia Europaea Gnesnensia, 2015)
The aim of this paper is to analyse non-places and heterotopias in the films “Cześć Tereska!” (Poland, 2001, Robert Gliński) and “Lilja 4-ever” (Sweden, 2002, Lukas Moodysson). Drawing on the theories of French anthropologist Marc Augé and philosopher Michel Foucault, the author demonstrates that the lives of the protagonists revolve around the ghetto-like housing estates of apartment blocks and non-places of hypermodernity. At the same time, despite the surrounding bleakness and fatalism, the heroines manage to find “havens” which perform the functions of heterotopia, in the sense proposed by Michel Foucault. The significance of both places is ambivalent, which is demonstrated in the discussion.